2004
DOI: 10.1177/0011128704264514
|View full text |Cite
|
Sign up to set email alerts
|

Race, Legal Representation, and Juvenile Justice: Issues and Concerns

Abstract: The objective of this study was to examine the influence of type of counsel across race on juvenile court outcomes. Using data from a sample of juvenile court referrals from two midwestern juvenile courts, this study examined the interaction of race and type of counsel on disposition outcome. The results indicated that youth without an attorney were the most likely to have the charges dismissed, and this effect was more pronounced for non-White youth. In addition, non-White youth represented by a private attor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 56 publications
2
33
0
Order By: Relevance
“…Juveniles with prior adjudications and prior arrests were more likely to have their cases petitioned. Similar to prior research (e.g., Frazier & Bishop, 1985;Guevara et al, 2004;Wordes et al, 1994), being detained after arrest resulted in an increased likelihood of petition.…”
Section: Resultssupporting
confidence: 76%
“…Juveniles with prior adjudications and prior arrests were more likely to have their cases petitioned. Similar to prior research (e.g., Frazier & Bishop, 1985;Guevara et al, 2004;Wordes et al, 1994), being detained after arrest resulted in an increased likelihood of petition.…”
Section: Resultssupporting
confidence: 76%
“…Even the landmark case extending criminal due process into juvenile cases, In re Gault (1967), identified only certain rights, requiring judges only to advise on the right to counsel in proceedings that might result in incarceration. Appointment of counsel is not required, and therefore states and localities demonstrate considerable variation in appointing lawyers to juvenile offenders (Guevara et al, 2004;US General Accounting Office, 1995).…”
Section: Non-punishment By Venuementioning
confidence: 99%
“…In some research, the influence of extralegal factors dissolves after legal factors are controlled (Belknap, 2001;Carter, 1979;Clarke & Koch, 1980;Dannefer & Schutt, 1982;Fenwick, 1982;Kempf-Leonard & Sontheimer, 1995;Phillips & Dinitz, 1982;Teilmann & Landry, 1981). However, other research has revealed that extralegal factors continue to influence juvenile court outcomes even when legal factors are included (Bishop, 2005;Bishop & Frazier, 1996;Bray, Sample, & Kempf-Leonard, 2005;Conley, 1994;Frazier & Bishop, 1995;Guevara, Herz, & Spohn, 2006;Guevara, Spohn, & Herz, 2004;Leiber, 1994;Thornberry & Christensen, 1984;Wordes & Bynum, 1995;Wordes et al, 1994). Pope and Feyerherm's (1990) review of 46 studies on juvenile court outcomes emphasized the need to take extralegal factors such as race into consideration.…”
Section: Research On Racial Disparities In Juvenile Court Outcomesmentioning
confidence: 99%